The Reporting of Child Abuse and Neglect in Ireland in an International Context. (20th September 2020) - Hanly, Conor
Abstract: Starting in the early 1990s, reports published over a quarter of a century detailed shocking levels of child abuse and child neglect in Ireland, along with failures by Church and State officials to take effective action. These revelations, supported by international research, made a compelling case for the introduction of some form of mandatory reporting. Yet until 2015, Ireland's child protection system relied upon the discretion of those who suspected incidents of child abuse. The Children First Act 2015 introduced a new system of mandatory reporting that applies to professionals working in the health, education, childcare and law enforcement fields, a system that became active at the end of 2017. This article reviews the development of the reporting system in Ireland, and analyses the new obligations created by the 2015 Act. The article also analyses some initial figures for 2018, which show a substantial increase in the number of reports of child abuse and neglect made in that year. Additionally, the article argues for the insertion into the new system of some nuance in order that victim autonomy might be better respected.